Towards Social Transformation: An Exploration of the Divergent Histories of Radicalism and Corporatizing Higher Education in Australia - Aidan Cornelius-Bell; Piper A. Bell (Ali Khorsandi Taskoh, 2023)
This article examines the continuing shift in higher education towards a corporate model under neoliberal policies, emphasising revenue and job readiness over social change. It highlights the historical role of students in campus activism for civil rights, Indigenous rights, and environmental issues, and how this is threatened by the corporatisation of universities. The article argues that the growing focus on corporate research partnerships, outputs, and international enrolments is leading to a more commercialised and capitalist education system, distancing universities from a role in addressing global challenges like climate change. It advocates for a renewed focus on transformative education, urging academics to work with students to develop organic intellectuals who apply knowledge to today's challenges. The article suggests that academics should support students as agents of social change, promoting transformative practices, rather than solely preparing them for the workforce. It acknowledges the challenges in shifting away from the current corporate idealism and calls for collective solidarity in reorienting higher education towards progressive social change. Ultimately, this article critically analyses the reluctance of higher education to embrace its potential as a tool for social transformation.